KAJIAN USAHATANI PADI SAWAH DI KELURAHAN TARATARA SATU KOTA TOMOHON - Gracella Kaparang; Jenny Baroleh; Rine Kaunang; Melissa L.G. Tarore (COCOS, 2015)
ABSTRACT  The objective of this research is to assess and describe the activities of the rice farming from the beginning to the harvesting stage, analyzing the farmers income and determine the feasibility of rice farming in the Taratara Satu Village, Tomohon Municipality.  The research was conducted during three months from February to April 2015, located in the Taratara Satu Village, Tomohon Municipality. The village samples purposive sampling (intentionally) and a sample of farmers using simple random sampling method (simple random). The research result showed the condition of rice farming in the Village of Taratara Satu Tomohon City, are land processing using tractors and cropping pattern’s applied Legowo row pattern, with the use of seed varieties Cigeulis, fertilization still relies on inorganic fertilizers and to eradicate the pest using pesticides.  Therefore, the rice farming in the Taratara Satu Village Tomohon Municipality profitable and feasible.  Key words : Rice Farming, Benefit, Feasibility